A Rare Case of Relapse Infective Endocarditis Caused by Granulicatella adiacens in Pregnancy - Wan Nor Aina Ar-Mardiyah Wan Jeffery; V. Rubini Nair Muthi @ P.S Muthialu; W Yus Haniff W Isa; Nazmi Liana Azmi (Asian Journal of Medicine & Health Sciences, 2023)
This is a case of a 33-year-old woman at her 12 weeks of pregnancy with underlying rheumatic heart disease presented with chest pain and diagnosed as infective endocarditis with Granulicatella adiacens bacteremia. She had a relapse of infective endocarditis complicated with splenic infarction, 6 weeks after the completion of intravenous ceftriaxone. She was put on another course of antibiotic regimen which consisted of intravenous ceftriaxone and gentamicin. She underwent elective lower segment caesarian section at 30 weeks of pregnancy and was discharged well. She had a valve surgery 3 months after the delivery.